Thermo-physical properties of liquids and gases over a heated rotating disk. (December 2022) - Khan, Mair; Salahuddin, T.; Awais, Muhammad; Al Alwan, Basem
Abstract: The motivation of this study arises due to huge occurrence of rotating disk in field of real-world processes like rotational air cleaner, turbomachinery, centrifugal pumps, aerospace engineering and chemical engineering. A numerical investigation is undertaken to study the thermo-physical properties of Newtonian fluid flow over a strongly heated rotating disk with temperature dependent viscosity. The solar radiative heat flux is considered in the heat equation. The temperature dependent viscosity and thermo-physical properties are assumed to explore the flow behavior. Numerical solutions of the converted boundary layer equations are then achieved by using fifth order Rung-Kutta Fehlberg integration approach with a shooting method. The attained results are discussed for mean flow profiles and physical interpretations of the problem are given through graphs and tables. It is observed that temperature dependence viscosity for liquids ranges to decrease the base flow profiles, whilst the gaseous viscosity nature has the opposite impact. The mass diffusion coefficient creates enhancement in concentration field. Moreover, correlations are plotted graphically in terms of temperature, concentration, and viscosity.